Prevalence of inter-arm blood pressure difference among clinical out-patients - Sharma, Balkishan; Ramawat, Pramila (International Journal of Health Sciences, 2016)
Objectives: An increased inter-arm blood pressure difference is an easily determined physical finding, may use as an indicator of cardio vascular event and other sever diseases. Authors evaluated 477 patients to determine the prevalence and significance of inter-arm blood pressure difference. Methodology: 477 routine outdoor patients selected to observe the inter-arm blood pressure difference. Age, height, weight, body mass index, history of disease and blood pressure recorded. Results: The prevalence of ≥10 mmHg systolic inter-arm blood pressure difference was 5.0% was more as compared to 3.8% had diastolic inter-arm blood pressure difference. The prevalence of systolic and diastolic inter-arm difference between 6 to 10 mmHg was 31.4% and 27.9% respectively. Mean systolic inter-arm blood pressure difference was significantly higher among those patients had a multisystem disorder (10.57±0.98 mmHg) and followed by patients with cardiovascular disease (10.22±0.67 mmHg) as compared to healthy patients (2.71±0.96 mmHg). Various diseases highly influenced the increase in blood pressure irrespective of systolic or diastolic was confirmed strongly significant (p<0.001) at different inter arm blood pressure difference levels. Conclusion: This study supports the view of inter-arm blood pressure difference as an alarming stage of increased disease risk that incorporated to investigate potential problems at an early diagnostic stage. A significant mean difference between left and right arm blood pressure recorded for many diseases. Key Words: Inter-arm Difference, Blood Pressure, Systolic Blood Pressure, Diastolic Blood Pressure, Cardio Vascular Disease